PLAYING AND THINKING ABOUT SOCCERS IN PHYSICAL EDUCATION CLASSES - Barreto, Mariama Silva Gouvêa (2023)
The study aimed to investigate the implementation of a didactic unit about soccers, with a group of 8th graders of elementary school, and analyze the education processes emerging from this intervention. It is about qualitative research like a research-action marked by the implementation of a didactic unit, composed of 12 classes, guided with the internal and external logic of soccer. The data product instrument used was the class diary, having as sources the participant observations and the audio records. The collected data were analyzed through the analysis of the codification categories in three steps: the organization and reading of the documents, codification and categorization of the materials. The results demonstrate that the soccers didactic unit enables the students to have positive and inclusive experiences, and a learning guided by body, conceptual and attitudinal knowledge, giving them access to the soccer sociocultural dimension through the external logic of the game.